Interprofessional education: does recent literature from rural settings offer insights into what really matters?. Issue 9 (September 2015) - Croker, Anne; Hudson, Judith N
<x xml:space="preserve">Abstract</x> Context As rural health staff of different disciplines often know one another and share workplace facilities, rural areas are well suited to the implementation of interprofessional education (IPE) strategies. Details of such strategies are often shared in journal articles so that educators can learn from and build on the experiences of others. A common theme in the apparent success of rural interprofessional initiatives concerns collaborative relationships among educators. However, do readers of journals see the full picture of the collaborative relationships among educators of different disciplines as they plan and implement strategies? Methods A literature interpretation informed by philosophical hermeneutics was used to explore the nature of educators' collaborative relationships in the planning and implementation of IPE initiatives as portrayed by authors of articles on rural IPE. Twenty‐four articles suitable for inclusion in the text set were identified through searches of databases and relevant journals. Results The nature of the collaborative relationships involved in planning and implementing educational strategies was rarely explicit. However, within an implied sense of interpersonal relationships, three themes were interpreted: grounded beginnings; untold stories, and anthropomorphised collectives. Conclusions Being explicit about educators' collaborative relationships may have potential to improve the transferability of IPE strategies to other contexts. A flowchart is presented to encourage authors to: (i) consider how to portray educators' collaborative relationships, and (ii) reflect on how these collaborative relationships may impact on the success, or otherwise, of their IPE projects.